2012
DOI: 10.1017/s0007114512004862
|View full text |Cite
|
Sign up to set email alerts
|

Cocoa polyphenols prevent inflammation in the colon of azoxymethane-treated rats and in TNF-α-stimulated Caco-2 cells

Abstract: Numerous lines of evidence support a relationship between intestinal inflammation and cancer. Therefore, much attention has recently been focused on the identification of natural compounds with anti-inflammatory activities as a strategy to suppress the early stages of colorectal cancer. Because cocoa is a rich source of bioactive compounds, the present study investigated its anti-inflammatory properties in a rat model of azoxymethane (AOM)-induced colon carcinogenesis and in TNF-a-stimulated Caco-2 cells. A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 49 publications
3
51
1
Order By: Relevance
“…In contrast, accumulating evidence has shown that some food types are protective against cancer, including oesophageal cancer, through their anti-inflammatory effects; e.g. soy protein inhibits inflammation by inhibiting the NF-κB and AKT signalling pathway [45], cocoa polyphenols prevent inflammation in the colon [46], olive oil and omega-3 fatty acids possess anti-inflammatory effects [47]. Increased risk by BMI may reflect the potential modulation of inflammation between diet, body composition, and oesophageal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, accumulating evidence has shown that some food types are protective against cancer, including oesophageal cancer, through their anti-inflammatory effects; e.g. soy protein inhibits inflammation by inhibiting the NF-κB and AKT signalling pathway [45], cocoa polyphenols prevent inflammation in the colon [46], olive oil and omega-3 fatty acids possess anti-inflammatory effects [47]. Increased risk by BMI may reflect the potential modulation of inflammation between diet, body composition, and oesophageal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…With their simpler structure and increased bioavailability, phenolic acids are one of the major (poly)phenol metabolites present in blood with a maximum plasma concentration of 0-4 µmol/L with an intake of 50 mg aglycone equivalents [62], and reported anti-inflammatory, anti-carcinogenic, anti-proliferative, anti-glycative and prebiotic properties in in vitro and/or in vivo studies [16,[62][63][64][65]. As the concentration in the colon is much higher than in the circulation with concentration ranging from 46 to 479 µmol/L in human faecal water [59,66], some effects exerted at high doses may still be physiological [67].…”
Section: Discussionmentioning
confidence: 99%
“…Polyphenol-rich apple diet administered to rats inhibited TNF-α, iNOS, IL-1β and IL-6 mRNA expression in the colon and diminished the number of CD68 cells [85] . Diet supplemented with cocoa polyphenols feed to rats with experimentally induced colon inflammation decreased the level of the nuclear NF-κB and of the pro-inflammatory enzyme COX-2 [86] . The role of natural products and their phytochemicals in modulation of molecular pathways involved at various stages of tumorigenesis has been summarized by Rajamanickam et al [87] .…”
Section: Resveratrolmentioning
confidence: 96%